Об абнормально факторизуемых конечных разрешимых группах - Васильев, А.Ф. (Український математичний журнал, 2002)
Вивчаються спадкові формації, замкнені відносно взяття добутків абнормальних підгруп скінченних розв'язних груп. Отримано опис розв'язних локальних спадкових формацій скінченних груп із даною властивістю. We study hereditary formations closed with respect to the operation of taking products of abnormal subgroups of finite solvable groups. We obtain a constructive description of solvable local hereditary formations of finite groups with the property indicated.